Iklim Komunikasi Organisasi dalam Menciptakan Lingkungan Kerja - Ni Kadek Dewi Sukmayanti; Putu Riana Artyanti Putri (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
In modern organizations, creating a comfortable and conducive work environment is crucial for maintaining employee performance and productivity. This study aims to examine the role of organizational communication climate in fostering a supportive and effective work environment. Using a qualitative literature review approach, the research synthesizes findings from previous studies on organizational communication and workplace conditions. The results indicate that a positive communication climate, characterized by support, participation in decision-making, trust, openness, and high-performance orientation, enhances employee motivation, collaboration, and overall work effectiveness. Support from supervisors and colleagues, involvement in organizational decisions, and transparent information sharing contribute to harmonious relationships and reduce potential conflicts. Additionally, a clear focus on performance goals ensures productivity and accountability across organizational units. The study highlights that implementing a constructive communication climate significantly impacts both individual and organizational outcomes. Limitations include reliance on literature from selected organizations, suggesting the need for broader empirical studies incorporating variables such as communication technology and organizational culture to deepen understanding of how communication climates shape effective and productive work environments.